Dl-3-n-Butylphthalide Ameliorates Diabetic Nephropathy by Ameliorating Excessive Fibrosis and Podocyte Apoptosis - Xu, Jingyu; Tang, Zonghao; He, Youwu; Cai, Shufang; Wang, Beini; Zhang, Susu; Wu, Man; Qian, Kai; Zhang, Kailun; Chai, Bo; Chen, Guorong; Xu, Ke; et al. (Frontiers in Pharmacology, 2021)
Diabetic nephropathy (DN) is a common diabetes associated complication. Thus, it is important to understand the pathological mechanism of DN and find the appropriate therapeutic strategy for it. Dl-3-n-Butylphthalide (DL-NBP) has anti-inflammatory and antioxidant effects, and been widely used for the treatment of stroke and cardiovascular diseases. In this study, we selected three different doses (20, 60, and 120 mg⋅kg−1 d−1) of DL-NBP and attempted to elucidate its role and molecular mechanism underlying DN. We found that DL-NBP, especially at the dose of 60 or 120 mg⋅kg−1 d−1, could significantly ameliorate diabetes-induced elevated blood urea nitrogen (BUN) and creatinine level, and alleviate renal fibrosis. Additionally, the elevated expressions of collagen and α-smooth muscle actin (α-SMA) in the kidney from db/db mice were found to be significantly suppressed after DL-NBP treatment. Furthermore, mechanistic studies revealed that DL-NBP inhibits pro-inflammatory cytokine levels, thereby ameliorating the development of renal fibrosis. Moreover, we found that DL-NBP could not only reduce the endoplasmic reticulum stress (ERS), but also suppress activation of the renin-angiotensin system to inhibit vascular endothelial growth factor (VEGF) level, which subsequently reduces the podocyte apoptosis in kidney of db/db mice. In a word, our findings suggest that DL-NBP may be a potential therapeutic drug in the treatment of DN.